157 Contemporary prescription opioid use among patients with systemic lupus erythematosus: a population-based cohort study. (April 2019) - Jorge, April; Lu, Na; Wallace, Zachary; Choi, Hyon
Abstract : Background: SLE is a chronic illness associated with pain and disability. Opioid use is associated with increased risk of addiction, abuse, and mortality in the general population. We assessed contemporary patterns of opioid prescribing among patients with SLE in a general population context and examined potential associations with opioid prescription use. Methods: Using a United Kingdom general population database, we conducted a cohort study of adult SLE patients, identified by Read codes. The exposures of interest were opioid prescriptions between January 1, 2007 and December 31, 2016. We classified opioids as weak, including tramadol and codeine, and strong, including hydrocodone, morphine, fentanyl, oxycodone, hydromorphone, and methadone. We examined the proportion of patients receiving prescriptions for weak and strong opioids and performed logistic regression to assess whether prescription use of these medications varied by age, sex, duration of SLE, other medication use for SLE, lifestyle exposures (alcohol and tobacco use), and socioeconomic status. We adjusted for age and sex. Results: Of 10, 784 SLE patients, (86% female, mean age 51.2 years), 32% were ever prescribed weak opioids (tramadol or codeine) and 10% were ever prescribed strong prescription opioids during the study period. 21% and 7% received multiple prescriptions for weak and strong opioids, respectively. Prescription opioid use was more common among older patients (adjusted OR 2.27 [95% CI 1.91–2.70] for weak opioid use and 2.94 [95% CI 2.14–4.03] for strong opioid use among patients over age 50 compared with those under age 30. (Table 1 ). SLE patients who were also taking NSAIDs, DMARDs, or glucocorticoids each had an increased odds of receiving prescription opioids. Current smokers were also more likely to be prescribed prescription opioids. There was no significant association found between deprivation score, a measure of socioeconomic status, and opioid usage. Conclusions: In this general population-based cohort study, nearly one-third of SLE patients were ever prescribed weak opioids and 10% were ever prescribed stronger opioids. This rate of opioid prescription use is higher among patients who are also taking NSAIDs, glucocorticoids, and DMARDs. These findings indicate the use of these potentially dangerous medications among a substantial portion of SLE patients. Future studies should assess the impact of opioid usage on mortality and other important outcomes among patients with SLE. Funding Source(s): NIH/NIAMS T32-AR-007258